Synthesis and characterization of new poly(ethyleneimine)‐g‐poly(methyl methacrylate) star‐block copolymers with hyperbranched cationic core. Issue 17 (14th June 2013) - Beckmann, Ralph; Beginn, Uwe
ABSTRACT Hyperbranched polyethyleneimine (hb‐PEI) is used as polymeric scaffold to synthesize new PEI‐g‐polymethylmethacrylate (PEI‐g‐PMMA) block copolymers, consisting of a hyperbranched, partially quarternized cationic core, and PMMA‐arms. The arms are grafted to the PEI scaffold by means of the "grafting to" method. Ammonium groups, covalently bond to the hyperbranched core, provide good adhesion to negatively charged surfaces, even in case of low‐surface charges. The PMMA strands provide compatibility of the macromolecules to PMMA matrices, hence generating potential dispersants, and compatibilizers for PMMA. A peculiar association behavior in organic solution is observed as supported by dynamic light scattering and DOSY measurements. First evidences of the applicability of the macromolecules as dispersants to prepare PMMA‐nanocomposites are given. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3700–3715